Association Between Irisin Level and Cognitive Function: A Systematic Review and Meta‐Analysis - Chengyan Han; Zining Zhou; Linlin Kong; Jing Lu; Xinyun Li (Brain and Behavior)
ABSTRACT Background Irisin is a newly discovered muscle factor, and more and more research has focused on the association between irisin and brain function. Our study aimed at investigating the correlation between irisin level and cognition. Methods Five electronic databases were searched for the correlation between irisin level and cognition in humans. The primary outcome was the correlation between irisin level and global cognition. Secondary outcomes were the correlation between irisin level and each cognitive domain, the correlation between brain‐derived neurotrophic factor (BDNF) level and global cognition, and the correlation between irisin level and BDNF level. Correlation coefficient (r) was used as effect size with its 95% confidence intervals (CI). Results There were a total of 11 articles that reported the correlation between irisin level and global cognition, and the pooled result showed a positive correlation among them (r = 0.26, 95% CI: 0.10–0.41). The subgroup analysis showed a positive correlation among non‐Asians (r = 0.28, 95% CI: 0.16–0.40), studies with small sample size (r = 0.35, 95% CI: 0.20–0.49), irisin measured from both serum (r = 0.32, 95% CI: 0.15–0.49) and cerebrospinal fluid (r = 0.27, 95% CI: 0.03–0.50), scales using Mini‐Mental State Examination (MMSE) (r = 0.36, 95% CI: 0.16–0.52), and study populations with diseases impairing cognition (r = 0.26, 95% CI: 0.07–0.43). Besides, our results indicated that there were no correlations between irisin level and cognitive domains, including immediate memory, short‐term memory, executive function, attention, language, and visual spatial ability (all p > 0.05). Additionally, the results suggested a positive correlation between BDNF level and global cognitive function (r = 0.27, 95% CI: 0.12–0.42), as well as the correlation between irisin level and BDNF level (r = 0.41, 95% CI: 0.24–0.56). Conclusions This study implied that irisin has a positive effect on cognitive function, and the mechanism may be associated with promoting the expression of BDNF.